2016
DOI: 10.1590/1806-9061-2016-0254
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Embryo Thermal Stimulation on the Serum Levels of Immunoglobulins and Corticosterone, and Organ Histopathology of 1 day-old Broilers

Abstract: Embryo thermal stimulation has been studied as a means to promote epigenetic changes and to improve broiler health and performance. This study aimed at evaluating immunoglobulin (IgM, IgG, and IgA) titers, serum corticosterone levels, and organ integrity of day-old male Cobb ® and Ross ® broilers. Embryos were submitted to hot and cold stimuli (thermal stimulation) on days 14-18 of incubation. The thermal manipulation treatments did not affect immunoglobulin titers of 1 dayold Cobb ® or Ross ® chicks, and caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
3
2
0
Order By: Relevance
“…Our results of reduced bursa weight resembled to those of Liu et al (2013) who also found that immune organ developmnet was reduced by application of high incubation temperature. In line with our findings another study reported that atrophy and lesions in bursa of day old chicks have been observed in response to "hot and slight hot" thermal stimulation of broiler embryos between ED14-18 with a TM duration of 3 and 2 h per day (Flores et al, 2016). In the study of Flores et al (2016) mean EST was measured as 38.8ºC for TM groups as similar to our experimental setting.…”
Section: Discussion Experimentssupporting
confidence: 91%
See 1 more Smart Citation
“…Our results of reduced bursa weight resembled to those of Liu et al (2013) who also found that immune organ developmnet was reduced by application of high incubation temperature. In line with our findings another study reported that atrophy and lesions in bursa of day old chicks have been observed in response to "hot and slight hot" thermal stimulation of broiler embryos between ED14-18 with a TM duration of 3 and 2 h per day (Flores et al, 2016). In the study of Flores et al (2016) mean EST was measured as 38.8ºC for TM groups as similar to our experimental setting.…”
Section: Discussion Experimentssupporting
confidence: 91%
“…In line with our findings another study reported that atrophy and lesions in bursa of day old chicks have been observed in response to "hot and slight hot" thermal stimulation of broiler embryos between ED14-18 with a TM duration of 3 and 2 h per day (Flores et al, 2016). In the study of Flores et al (2016) mean EST was measured as 38.8ºC for TM groups as similar to our experimental setting. One of the reason might be that Increased temperature might have activated the body's endocrine system of hypothalamic-pituitary-adrenal (HPA) development resulting in reduced immune function which repressed bursa growth (Gong & Zhong, 2009).…”
Section: Discussion Experimentssupporting
confidence: 91%
“…The strong increase in the serum globulin concentration may be associated with the improving immune status of the birds in the post hatch period, Lisano and Kennamer (1977). This finding is in line with Flores et al, (2016) who found the highest immunoglobulin (IgM) titer was obtained in chicks from 36 wks old breeders, and the lowest, in chicks from 53 wks old breeders, while no differences in immunoglobulin (IgG, or IgA) titer were observed between breeder ages in Ross chicks.…”
Section: Effect Of Biotin Dosesupporting
confidence: 81%
“…While an increase in corticosterone levels resulting from postnatal conditioning improved heat tolerance at day 42, a decrease in corticosterone levels resulting from prenatal conditioning caused a strong negative effect. Flores et al (2016) observed severe bursal lesions in thermally stimulated embryos (þ1-1.4 8C for 2-3 h/day on days 16-18 of embryonic development). These bursal lesions presented similar characteristics as those caused by infectious bursal disease.…”
Section: Discussionmentioning
confidence: 86%